Prevalence of subclinical mastitis in production systems dual purpose cattle in Matepiña village, Arauca, Colombia (Revista Sistemas de Producción Agroecológicos, 2014)
In Arauca Department, specifically in the town of Arauca, have not done enough research on mastitis in cattle production systems, it is necessary that the region of the state and hears milk quality as this directly affects the health and status of livestock in general, for this reason this research was conducted in Matepiña path, which consists of 10 farms that have been implementing major technological packages strengthening livestock in the region. This trail has 2810 head of cattle of which 830 are females and 240 are in production. Proof of California Mastitis Test (CMT) was performed, it was determined that the prevalence of mastitis is 54.6% plus etiologic agents in the positive to the CMT test udders were isolated. It was established that the principal agent of the 247 positive mammary quarters isolated in the laboratory was Staphylococcus aureus with 43.72% corresponding to 108 infected mammary quarters. The second pathogen was Staphylococcus epidermis 82/4 with 33.20%, followed by Corynebacterium bovis was found in 19 quarters being 7.70% of the positive samples. Subsequently, at 17 quarters Streptococcus agalactiae (6.89%), Corynebacterium pyogenes in 11 quarters (4.45%) and isolated lesser proportion Streptococcus disgalactiae and Escherichia coli of seven and three quarters which corresponds to 2.83% and 1.21% respectively. It could stipulate as in other research that farms with a high prevalence of subclinical mastitis, have great management problems. Mastitis is a disease to prevent, not to try, since you can control considering that it is primarily a management problem, so that should make great efforts to avoid it, by sanitary measures in the phases of pre-milking, milking and post-milking, because they are critical of the process by high risk of infection among animals affected and healthy, reducing the number of cases of clinical mastitis in a herd sub ​​clinical.
Keywords: milk; subclinical mastitis; pathogens